Living landscapes and cultural landmarks world heritage sites in the Philippines - Villalon, Augusto F.; Oshisma, Neal M. ([Manila] Art Post Asia, 2006)
Of the many tropical wonders of the Philippine archipelago, the Tubbataha Reef National Marine Park and the Puerto Princesa Subterranean River National Park in Palawan, as two of the richest eco-regions teeming with diverse indigenous plant and animal life, have been designated by UNESCO among the five World Heritage Sites in the Philippines. The other World Heritage cultural sites that belong to the country are: the Rice Terraces of the Philippine Cordilleras, the Historic Town of Vigan in Ilocos, and the Baroque Churches in the Philippines specifically Santo Tomás de Villanueva in Miag-ao, Iloilo; San Agustín in Paoay, Ilocos Norte; Nuestra Senora de la Asunción in Santa Maria, Ilocos Sur; and San Agustín in Intramuros, Manila. Living Landscapes and Cultural Landmarks provides a sharp pictorial focus for the first time on the World Heritage Sites in the Philippines, as image after image pulsates with the country's exotic natural life, the indigenous culture and cultivation of the land, and the faith and lives of people during the Spanish era.
What is the world heritage site? -- Natural heritages sites -- Tubbataha Reef National Marine park -- Puerto Princesa Subterranean River National park -- Cultural heritage sites -- Baroque churches of the Philippines -- San Agustin, Intramuros, Manila -- San Tomás de Villanueva, Miag-ao,Iloilo -- San Agustin, Paoay, Ilocos Norte -- Nuestra Señora de la Asunción, Santa María, Ilocos Sur -- Rice Terraces of the Philippines Cordilleras -- Historic town of Vigan -- Tentative list of world heritages sites in the Philippines -- Index -- Acknowledgments.
Includes index.
Keywords: World Heritage areas -- Philippines; Historic buildings -- Philippines